Orthography, phonology, morphology, and meaning - Frost, Ram.; Katz, Leonard; ScienceDirect eBooks (Amsterdam ; New York : North-Holland, 1992)
The area of research on printed word recognition has been one of the most active in the field of experimental psychology for well over a decade. However, notwithstanding the energetic research effort and despite the fact that there are many points of consensus, major controversies still exist. This volume is particularly concerned with the putative relationship between language and reading. It explores the ways by which orthography, phonology, morphology and meaning are interrelated in the reading process. Included are theoretical discussions as well as reviews of experimental evidence by leading researchers in the area of experimental reading studies. The book takes as its primary issue the question of the degree to which basic processes in reading reflect the structural characteristics of language such as phonology and morphology. It discusses how those characteristics can shape a language's orthography and affect the process of reading from word recognition to comprehension. Contributed by specialists, the broad-ranging mix of articles and papers not only gives a picture of current theory and data but a view of the directions in which this research area is vigorously moving.
Linguistic awareness and orthographic form / Ignatius G. Mattingly -- Reading consonants and guessing vowels : visual word recognition in Hebrew orthography / Ram Frost and Shlomo Bentin -- Basic processes in reading : is the orthographic depth hypothesis sinking? / Derek Besner and Marilyn Chapnik Smith -- The reading process is different for different orthographies : the orthographic depth hypothesis / Leonard Katz and Ram Frost -- Beyond orthographic depth in reading : equitable division of labor / Mark S. Seidenberg -- Automatic activation of linguistic information in Chinese character recognition / Daisy L. Hung, Ovid J.L. Tzeng, and Angela K.Y. Tzeng -- Orthographic neighborhoods and visual word recognition / Jonathan Grainger -- On the role of cohorts or neighbors in visual word recognition / Neal F. Johnson -- The relation of speech to reading and writing / Alvin M. Liberman -- On the relations between learning to spell and learning to read / Donald Shankweiler and Eric Lundquist -- Phonological awareness, reading, and reading acquisition : a survey and appraisal of current knowledge / Shlomo Bentin -- Can theories of word recognition remain stubbornly nonphonological? / Claudia Carello, M.T. Turvey, and Georgije Lukatela -- Reading in English and Chinese : evidence for a "universal" phonological principle / Charles A. Perfetti, Sulan Zhang, and Iris Berent -- "Assembled" phonology and reading : a case study in how theoretical perspective shapes empirical investigation / Guy C. Van Orden [and others] -- Dual-route models of print to sound : red herrings and real horses / Kenneth R. Paap, Ronald W. Noel, and Linda S. Johansen -- Strategies and stress assignment : evidence from a shallow orthography / Lucia Colombo and Patrizia Tabossi --Morphological analysis in word recognition / Laurie B. Feldman and Darinka Andjelković -- Units of representation for derived words in the lexicon / Cristina Burani and Alessandro Laudanna -- Representation and processing of morphological information / Cecile Beauvillain and Juan Segui -- Bilingual lexical representation : a closer look at conceptual representations / Annette M.B. de Groot -- Memory-addressing mechanisms and lexical access / Kenneth Forster.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Language and languages -- Orthography and spelling; Grammar, Comparative and general -- Phonology; Lexicology; Psycholinguistics; Language; Psycholinguistics; Orthographe; Phonologie; Lexicologie; Psycholinguistique; LANGUAGE ARTS & DISCIPLINES -- Alphabets & Writing Systems; LANGUAGE ARTS & DISCIPLINES -- Spelling; Grammar, Comparative and general -- Phonology; Language and languages -- Orthography and spelling; Lexicology; Psycholinguistics; Spelling; Morfologie (taalkunde); Fonologie; Schriftzeichenerkennung; Psycholinguistik; Rechtschreibung; Aussprache; Aufsatzsammlung; Psycholinguistique; Langage -- Acquisition; Orthographe; Mots, Reconnaissance des; Conscience linguistique; Psycholinguistics; Electronic books